Application of Functional Magnetic Resonance Imaging in the Diagnosis of Parkinson’s Disease: A Histogram Analysis - Shi, Dafa; Zhang, Haoran; Wang, Siyuan; Wang, Guangsong; Ren, Ke (Frontiers in Aging Neuroscience, 2021)
This study aimed to investigate the value of amplitude of low-frequency fluctuation (ALFF)-based histogram analysis in the diagnosis of Parkinson’s disease (PD) and to investigate the regions of the most important discriminative features and their contribution to classification discrimination. Patients with PD (n=59) and healthy controls (HCs) (n=41) were identified and divided into a primary set (80 cases, including 48 patients with PD and 32 HCs) and a validation set (20 cases, including 11 patients with PD and 9 HCs). The Automated Anatomical Labeling 116 atlas was used to extract the histogram features of regions of interest in the brain. Machine learning methods were used in the primary set for data dimensionality reduction, feature selection, model construction, and model performance evaluation. The model performance was further validated in the validation set. After feature data dimension reduction and feature selection, 23 of a total of 1276 features were entered in the model. The brain regions of selected features included the frontal, temporal, parietal, occipital and limbic lobes, as well as the cerebellum, and thalamus. In the primary set, the area under the curve (AUC) of the model was 0.974, the sensitivity was 93.8%, the specificity was 90.6%, and the accuracy was 93.8%. In the validation set, the AUC, sensitivity, specificity, and accuracy were 0.980, 90.9%, 88.9%, and 90.0%, respectively. ALFF–based histogram analysis can be used to classify patients with PD and HCs and to effectively identify abnormal brain function regions in PD patients.